Factors contributing to taxpayer morale: a multi-country perspective - Kosiorek, Jakub (Rhodes University, Faculty of Commerce, Department of Accounting, 2018)
Tax morale is the intrinsic motivation to pay taxes that arises either from a belief that one should contribute towards society by paying taxes or from a moral obligation to pay taxes. The goals of this thesis were to identify the various factors that influence tax morale in a country and use these factors in order to attempt to determine whether tax morale in South Africa has improved or deteriorated over the years. A further goal of this thesis was to identify strategies that could be implemented by a country in order to improve the tax morale of its citizens. The period covered by this thesis is between the years 2000 and 2015. The factors that have an effect on tax morale were identified by a review of the literature. It was found that a number of factors appear to have an impact on tax morale, but certain of these factors are incapable of being directly influenced by tax administrations. With regard to South Africa, it was found that a number of factors affecting tax morale appear to have improved over the years, while others had deteriorated. However, overall it appeared that tax morale in South Africa had deteriorated. With regard to strategies that could be used to improve tax morale, a number were identified by reviewing the literature and include strategies implemented in certain countries, as well as those discussed by scholars. Ii was found that South Africa had implemented a number of the strategies aimed at improving tax morale in its own tax system, but the manner in which some of them were implemented could have been improved. Furthermore, a number of strategies were identified that South Africa has not yet implemented and thus should look to attempting to implement these strategies to improve tax morale.
Keywords: Taxpayer compliance -- South Africa; Tax evasion -- South Africa; Taxpayer compliance -- Social aspects -- South Africa; Taxpayer compliance -- Economic aspects -- South Africa; Tax morale -- South Africa